2022
DOI: 10.1101/2022.10.27.514020
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Benchmarking solutions to the T-cell receptor epitope prediction problem: IMMREP22 workshop report

Abstract: Many different solutions to predicting the cognate epitope target of a T-cell receptor (TCR) have been proposed. However several questions on the advantages and disadvantages of these different approaches remain unresolved, as most methods have only been evaluated within the context of their initial publications and data sets. Here, we report the findings of the first public TCR-epitope prediction benchmark performed on 23 prediction models in the context of the ImmRep 2022 TCR-epitope specificity workshop. Th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…We showed that this model achieved comparable performance to the one of NetTCR, while being very simple. These results align with previous findings ( 17 , 26 , 29 , 30 ). A closer analysis of our results revealed that TCRbase performed at par with NetTCR when separating positive versus 10X negative TCRs; however, the gap in performance between the two models was enlarged on the positives versus swapped negatives prediction task, where NetTCR significantly outperformed TCRbase.…”
Section: Discussionsupporting
confidence: 93%
“…We showed that this model achieved comparable performance to the one of NetTCR, while being very simple. These results align with previous findings ( 17 , 26 , 29 , 30 ). A closer analysis of our results revealed that TCRbase performed at par with NetTCR when separating positive versus 10X negative TCRs; however, the gap in performance between the two models was enlarged on the positives versus swapped negatives prediction task, where NetTCR significantly outperformed TCRbase.…”
Section: Discussionsupporting
confidence: 93%
“…prediction whether random TCRs bind to a specific peptide). Meysman et al have compared superficially different approaches to TCR-pMHC binding (17), but also raised the importance of a truly independent benchmark. They reveal that additional information like CDR1/2 improved the prediction, but they did not investigate the role that imbalance, size or overtraining might have on model performance by using those additional features within the used dataset.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, one uses CDR3 α sequences from healthy TCR repertoires and samples of antigen-specific CDR3 α as respectively the background and the selected dataset. DiffRBM models for the α chain reach a discrimination performance comparable to the one for the β chain, as shown in [Meysman et al, 2022]. On the same footing, with single-cell TCR sequencing data becoming increasingly available, our approach could also be extended to modeling the pairs of TCR α and β chains, which have been suggested to play a synergistic role in determining antigen specificity [Carter et al, 2019, Montemurro et al, 2021, Milighetti et al, 2021].…”
Section: Discussionmentioning
confidence: 92%
“…An approach like diffRBM (similarly to SONIA) returns peptide-specific models and hence needs to be trained on TCRs known to recognize a certain peptide for any prediction of specificity to that peptide. Furthermore, the performance by diffRBM decreases compared to other methods when we look at a different task, the one of discriminating a set of antigen-specific receptors from receptors with another antigen specificity [Meysman et al, 2022]. This is due to the fact that our approach, in contrast to other methods [Gielis et al, 2019, Montemurro et al, 2021, Weber et al, 2021], is unsupervised, meaning that it is not trained using receptors of different antigen specificity as negatives against which the positives should be discriminated.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation